A throughput-oriented reliable multicast in multi-rate wireless networks. (2018) - Hassouna, Asma Ben; Koubaa, Hend; Saidane, Leila Azouz
As low transmission delays can meet the requirements of many applications, high-throughput is the request of various others. Therefore, with consideration of the multi-user diversity (MUD) and the wireless broadcast advantage (WBA) features, we deal with the problem of maximising the multicast throughput. Hence, we introduce two new rate-aware multicast metrics: EMTH and XMTH. EMTH helps to choose the transmission rates that estimate the best multicast throughput expected. XMTH can reach extreme throughput values if the high computational needs are satisfied. Both metrics carry out a rate adaptation process and take into consideration the link reliabilities. They can be used to choose multi-rate multicast schemes and to decide reliable multicast paths. Results show that the proposed metrics give the best system performance in terms of throughput. They confirm that, using EMTH and XMTH, it is possible to trade-off a very good throughput improvement for an insignificant delay increase.